A Forward-Looking Study on the correlates of Postoperative Pain after Retrograde Intrarenal Surgery with FANS for Kidney Stones - Dr. Kaustubh Gupta; Dr. Akash Verma; Dr. Nishant Ranjan; Dr. Nikhil Kumar Gupta (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Retrograde Intrarenal Surgery with FANS (flexible and navigable suction ureteric access sheath) is increasingly favored for treating renal calculi due to its minimally invasive nature and high stone-free rates. Despite reduced morbidity compared to traditional methods, postoperative pain remains a challenge. This prospective study aimed to evaluate patient-related, stone-related, and operation-related factors that predict severe postoperative pain following RIRS with FANS. Methods: A total of 97 patients (aged 18–65) with radiologically confirmed renal stones underwent RIRS at our center between March 2021 and September 2022. Preoperative data included demographics, stone characteristics (number, size, location, density), hydronephrosis, and stent status. All procedures utilized a 7.5 Fr flexible digital ureteroscope, Holmium:YAG laser lithotripsy and 10/12 fr flexible and navigable suction ureteric access sheath . Postoperative pain was assessed via the Visual Analogue Scale (VAS) at 6, 12, and 24 hours. Patients requiring additional analgesia with VAS ≥7 were categorized as having severe pain (Group II), whereas those with VAS <7 were grouped as mild pain (Group I). Associations between potential predictors and pain scores were analyzed using SPSS version 25 (p<0.05 was considered significant). Results: Among the 97 participants, 84.5% had VAS <7 (Group I) and 15.5% reported VAS ≥7 (Group II). No significant differences were noted in age, gender, stone location, stone size, or preoperative hydronephrosis between the groups (p>0.05). Two operation-related factors emerged as significant: smaller-diameter ureteral access sheaths (p=0.027) and prolonged sheath indwelling time exceeding 60 minutes (p=0.043) correlated with higher postoperative pain. Conclusion: Technical factors—namely ureteral access sheath size and sheath indwelling time—were key predictors of postoperative pain following RIRS with FANS. Identifying high-risk patients preoperatively may guide refined surgical approaches and more targeted analgesic protocols, ultimately improving patient comfort and overall satisfaction.